2014
DOI: 10.3174/ajnr.a3920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Remodeling (Retraction and Recoil) of the Pipeline Embolization Device on Aneurysm Occlusion Rate

Abstract: BACKGROUND AND PURPOSE:During endovascular treatment of unruptured aneurysms with the Pipeline Embolization Device, an oversized device is often selected to achieve better wall apposition; however, this device oversizing could be related to overelongation and possible delayed enlargement of the stented region. The purpose of this study is to investigate the relationship between oversize and treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…This phenomenon usually is referred to as ''fish-mouthing'' and describes tapering of one or both ends of an FDS. 23 The finding can be visualized best in either DSA or FD-CT. In our survey, we found fish-mouthing in three cases (6.9%).…”
Section: Occlusion Rates and Patient Outcomementioning
confidence: 99%
“…This phenomenon usually is referred to as ''fish-mouthing'' and describes tapering of one or both ends of an FDS. 23 The finding can be visualized best in either DSA or FD-CT. In our survey, we found fish-mouthing in three cases (6.9%).…”
Section: Occlusion Rates and Patient Outcomementioning
confidence: 99%
“…5 The nominal MCR for the pipeline embolization device (PED) is 30 $ 35%; 6 that is, nearly one-third of ostium is covered by the device. The true MCR of a deployed PED may differ from the nominal MCR due to device oversize, 7 manipulation of device, 8 deformation caused by vessel curvature, 7 or aneurysm location. At the curved or dilated section of an artery, where intracranial aneurysms are often located, wires of the PED are farther apart, and the MCR is lower than those at other regions.…”
Section: Background and Purposementioning
confidence: 99%
“…Moreover, Jou et al and Mut et al focused only on the stent oversizing and increasing flow [10,21]. However, in the study by Jou et al, 50% of the cases showed that the occlusion occurred at an oversizing of less than 1 mm.…”
Section: Clinical Aspect From the Results In Comparison With Those Ofmentioning
confidence: 99%
“…Jou et al, using the data from 14 aneurysms, statistically described that oversized artery by stenting may lead to the incomplete occlusion [21]. They showed that artery oversized by 1 mm did not yield occlusion.…”
Section: Clinical Aspect From the Results In Comparison With Those Ofmentioning
confidence: 99%